1996
DOI: 10.1046/j.1365-2141.1996.421961.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum erythropoietin levels in paroxysmal nocturnal haemoglobinuria: implications for therapy

Abstract: In order to assess the rationale and possible indications for the use of recombinant erythropoietin in paroxysmal nocturnal haemoglobinuria (PNH), we have measured endogenous erythropoietin (Epo) levels in 18 patients with PNH and in 44 patients with iron deficiency anaemia (IDA). In both groups of patients we found a significant inverse correlation between Epo and haemoglobin (Hb). However, the mean Epo level was significantly higher in the PNH group (385 mU/ml) than in the IDA group (136 mU/ml). The range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…Thus, strategies for iron chelation are not necessary; in fact these patients may sometimes even require iron supplementation to sustain the compensatory erythropoiesis (Rosse 1982). Similarly, vitamin B12 and folate supplementation are usually indicated to sustain the enhanced erythropoiesis (Rosse 1982); furthermore, endogenous erythropoiesis may also be increased by recombinant erythropoietin, mostly in cases with inadequate production (Stebler et al 1990; Bourantas 1994; McMullin et al 1996). Paradoxically, all these strategies, including iron replacement, may lead to increased hemolysis as a result of increased PNH hematopoiesis, contrary to what is seen following suppression of erythropoiesis by transfusions.…”
Section: Management: the Pre-eculizumab Eramentioning
confidence: 99%
“…Thus, strategies for iron chelation are not necessary; in fact these patients may sometimes even require iron supplementation to sustain the compensatory erythropoiesis (Rosse 1982). Similarly, vitamin B12 and folate supplementation are usually indicated to sustain the enhanced erythropoiesis (Rosse 1982); furthermore, endogenous erythropoiesis may also be increased by recombinant erythropoietin, mostly in cases with inadequate production (Stebler et al 1990; Bourantas 1994; McMullin et al 1996). Paradoxically, all these strategies, including iron replacement, may lead to increased hemolysis as a result of increased PNH hematopoiesis, contrary to what is seen following suppression of erythropoiesis by transfusions.…”
Section: Management: the Pre-eculizumab Eramentioning
confidence: 99%
“…6 However, the level usually depends on the cause of anaemia, with higher levels in aplastic anaemia compared to the lower levels found in haemolytic anaemia. 7 This may suggest a case for a trial of erythropoietin in haemolytic anaemia when there may be a suboptimal endogenous drive. 7 The erythropoietin level at the start of treatment is not a reliable indicator of response to erythropoietin.…”
Section: Discussionmentioning
confidence: 99%
“…7 This may suggest a case for a trial of erythropoietin in haemolytic anaemia when there may be a suboptimal endogenous drive. 7 The erythropoietin level at the start of treatment is not a reliable indicator of response to erythropoietin. However, some studies on the use of cancer-related anaemia have suggested that those with levels 4500 U/l are less likely to respond, with the best results achieved if the erythropoietin level is below 100 U/l.…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors have a blunted effect because of the underlying marrow defect. There is a suggestion that recombinant erythropoietin may have a use in patients with high transfusion requirements [40], although serum erythropoietin levels are very high in PNH patients, similar to levels found in AA [41]. …”
Section: Clinical Featuresmentioning
confidence: 99%